The Photothermal Effect of a Single Gold-magnetic Nanocrescent in A Glycerol-water Mixture Media - Xuan Hoa, Vu; Thu Ha, Pham Thi; Trang, Tran Thu (VNU Journal of Science: Mathematics - Physics, 2023)
The photothermal effect of gold nanostructures has been majority known as the nanothermal effect of gold clusters under laser irradiation. However, there are still many challenges to measuring the local temperature generated by a single nano gold in a complex media. In this work, a gold magnetic nanocrescent (G-MNC) has been studied, it composed of a superparamagnetic iron oxide core and gold shell with a size of 170 nm in glycerol/water (80:20), under 650 nm laser irradiation. Using rotational scattering correlation spectroscopy (RSCS), a sophisticated technique has been developed, the local temperature generated by only single magnetic nanocrescent was measured. The dependence of the heat generation according to the power of the laser shows that the heat generated by the gold NC is proportional to the power of the laser, and the maximum temperature was 19.5 o C, corresponding to the laser power was 29×10 3 W.cm -2 . Under using the proper laser irradiation to the plasmon resonance, G-MNCs act as nano thermometers. The photothermal effect of the single G-MNC was implemented in a mixing solution of glycerol and water.